2019
DOI: 10.3389/fpsyg.2019.00141
|View full text |Cite
|
Sign up to set email alerts
|

Causal Interactive Links Between Presence and Fear in Virtual Reality Height Exposure

Abstract: Virtual reality plays an increasingly important role in research and therapy of pathological fear. However, the mechanisms how virtual environments elicit and modify fear responses are not yet fully understood. Presence, a psychological construct referring to the ‘sense of being there’ in a virtual environment, is widely assumed to crucially influence the strength of the elicited fear responses, however, causality is still under debate. The present study is the first that experimentally manipulated both variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
54
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 65 publications
11
54
0
1
Order By: Relevance
“…The results showed a decrease of the parasympathetic and an increase Virtual reality evoked emotional reactions through the effects of immersion and the presence in VR environments. Previous studies have shown that in moderate-intensity stress, VR scenarios evoked a sympathetic activity [15][16][17][18]. In the present study, these data were confirmed; the current results showed that electrodermal amplitude and the number of fluctuations were increased in the most stressful ISS scenario in one subject, reflecting the increase in sympathetic activity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results showed a decrease of the parasympathetic and an increase Virtual reality evoked emotional reactions through the effects of immersion and the presence in VR environments. Previous studies have shown that in moderate-intensity stress, VR scenarios evoked a sympathetic activity [15][16][17][18]. In the present study, these data were confirmed; the current results showed that electrodermal amplitude and the number of fluctuations were increased in the most stressful ISS scenario in one subject, reflecting the increase in sympathetic activity.…”
Section: Discussionsupporting
confidence: 89%
“…Free movement in a VE increases the number of blinks and the amplitude of EDA, heart rate, and tachygastric power, and decreases bradygastric power, respiratory sinus arrhythmia, finger temperature, and respiratory rate [13,14]. Similar effects of sympathetic activation were found in the virtual Roller Coaster [15,16] or simulated in VR high places [17,18].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…The results further demonstrated that post-test AQ scores depended quadratically on time spent practicing, but not with the number of sessions practiced, indicating that it might be more important to play one level for a longer period of time instead of practicing many VR levels. Moreover, it was shown that, in line with previous research, a higher presence was associated with better outcomes [23].…”
Section: Discussionsupporting
confidence: 83%
“…Only the relation between proportion of completed modules and outcome emerged as a consistent association [15,16]. Previous research into VR treatment indicated that presence plays an important role in the effectiveness of a program [23]). For example, in our study reporting the main results of this trial we found that a larger reduction in acrophobia symptoms was associated when the feeling of being present in the virtual environment was higher [1].…”
Section: Introductionmentioning
confidence: 81%